Nursing Care for Homeless Patients with Hemorrhagic Stroke at A Public Hospital - Dwivania, Agatha Tunjung; Ernawati, Ernawati; Zendrato , Mey Lona Verawaty; Marpaung , Yosi Marin (Universitas Prima Indonesia, 2024)
A hemorrhagic stroke occurs when a blood vessel in the brain bursts, causing bleeding in the brain tissue. A hemorrhagic stroke can have a significant impact on the patient. Family support has been shown to influence the success of treatment for hemorrhagic stroke patients. Therefore, Family support is substantial and linked to achieving patient independence. Homeless stroke patients typically receive minimal care and have high mortality rates. This paper aims to review the implementation of care for homeless patients with hemorrhagic stroke in a public hospital in Jakarta. This article is a case report of a homeless 65-year-old man with decreased consciousness who was diagnosed with hemorrhagic stroke. The data were obtained by physical assessment. Several diagnostic tests were performed, including CT scan, MRI, and blood tests. A student nurse working one shift per day provided nursing care for three days. The patient had limb paralysis and drowsiness. The priority diagnoses were ineffective cerebral tissue perfusion, impaired physical mobility, and deficits in self-care. Nursing care focuses on the patient's consciousness and fulfilling basic needs. After 3 days of care, the patient was still unconscious. However, there were no symptoms of increased intracranial pressure. Family participation is necessary for the care of patients with hemorrhagic stroke. The nurse's role as a caregiver becomes primary and crucial for homeless patients who have no family.